Users perceptions and acceptance of small scale postharvest technologies in developing countries: a conceptual framework - Morris, Kwami Justina Kenobi; Kamarulzaman, Nitty Hirawaty; Mohamed, Zainal Abidin; Mohd Nawi, Nolila; Man, Norsida (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Despite the existence of small scale postharvest losses (PHLs) reduction technologies, reports of continual PHLs are still prevalent in developing countries. This paper presents a new and multidisciplinary conceptual framework for understanding users’ perceptions and acceptance of small scale postharvest technologies. The proposed framework is necessary to enable future development of successful postharvest technologies as well as fine-tuning of existing ones to increase their success rates.